Home care services for elderly patients with chronic diseases: A narrative literature review - Haidar, Muhammad; Chayati, Nur (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Comprehensive and continuous health services are provided to individuals and families in their place of residence to improve, maintain, or restore health, increase independence, and minimize the impact of disease. In Indonesia, the number of elderly people is increasing. Health services for older people should be a priority, along with the increasing number of elderly people. In terms of health services, older people need help. In addition, the elderly are more susceptible to various diseases, including degenerative and chronic diseases. Purpose: To determine the description of home health services for elderly patients with chronic diseases. Method: This study searched the following bibliographic databases to identify potentially relevant documents: Scien Direct, Pubmed, and MDPI publications in 2020-2024. Findings from the studies were extracted and compiled, guided by the Joanna Briggs Institute (JBI). Literature review using the Scien Direct, Pubmed, and MDPI databases. Keywords: